The Effect of Oral Administration of Green Tea Leaf Extract (Camellia Sinensis) on Leptin and Adiponectin Hormone Levels in Obese Male Wistar Rats (Rattus Norvegicus): A Literature Review - Fiona Suryo; Agus Eka Darwinata; I Wayan Sumardika (Riviera Publishing, 2026)
Green tea (Camellia sinensis) has attracted considerable attention as a natural anti-obesity agent due to its rich bioactive compounds, including catechins, epigallocatechin gallate (EGCG), flavonoids, polyphenols, and caffeine. This review aimed to analyze the effects of oral administration of green tea leaf extract on leptin and adiponectin hormone levels in obese male Wistar rats (Rattus norvegicus) and to evaluate its underlying anti-obesity mechanisms. This study employed a structured literature review method using experimental articles published between 2015 and 2025, obtained from PubMed, Google Scholar, ScienceDirect, Scopus, and Garuda databases. The selected studies focused on obese animal models receiving oral green tea extract interventions, with outcomes related to leptin, adiponectin, body weight, lipid metabolism, insulin resistance, and adiposity. The reviewed studies consistently demonstrated that oral administration of green tea extract reduced leptin levels and increased adiponectin concentrations in obese male Wistar rats. These effects were associated with reduced visceral fat accumulation, enhanced fatty acid oxidation, improved insulin sensitivity, and better lipid profiles. Mechanistically, green tea bioactive compounds activated AMP-activated protein kinase (AMPK), inhibited adipogenesis, stimulated thermogenesis and fat browning, and reduced oxidative stress and inflammation. Several studies also reported significant reductions in body weight gain, triglycerides, cholesterol levels, and hepatic lipid accumulation following green tea supplementation. In conclusion, green tea leaf extract possesses significant anti-obesity potential through modulation of leptin and adiponectin hormones and improvement of metabolic function in obese male Wistar rats.